2009
DOI: 10.1002/erv.940
|View full text |Cite
|
Sign up to set email alerts
|

Unfavourable family characteristics and their associations with childhood obesity: A cross‐sectional study

Abstract: Familial factors have moderate ability to predict children's weight status. There is a need to identify other familial mechanisms taking into account developmental and temporal evolutions over the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 41 publications
4
88
1
2
Order By: Relevance
“…58 Other parental stressors that influence BMI levels in children include violence, serious life events, food or housing insecurity, maternal depression or substance abuse, and paternal incarceration. [59][60][61][62][63][64][65][66][67] For many studies, SES was a controlled variable in order to determine associations with other psychosocial stressors, but an article by Garasky et al 68 found that financial strain was positively associated with children being overweight or obese.…”
Section: Sleepmentioning
confidence: 99%
“…58 Other parental stressors that influence BMI levels in children include violence, serious life events, food or housing insecurity, maternal depression or substance abuse, and paternal incarceration. [59][60][61][62][63][64][65][66][67] For many studies, SES was a controlled variable in order to determine associations with other psychosocial stressors, but an article by Garasky et al 68 found that financial strain was positively associated with children being overweight or obese.…”
Section: Sleepmentioning
confidence: 99%
“…A number of studies have examined early nutrition, including breastfeeding, and associations with obesity with conflicting results (1)(2)(3)(4)(5)(6)(7)(8)(9) . Differences in findings are likely due to a lack of control for confounding variables, small sample size, socioeconomic status and other differences such as subject age at time of measurement and family structure (10) .…”
mentioning
confidence: 99%
“…Children exposed to high food consumption or to consumption of high caloric food and sugary drinks, tend to grow up with such eating patterns and food preferences that were formed early in life. Similarly, families consuming few fruits and vegetables or none at all, tend to pass these eating habits to their children [171,172].…”
Section: Family and Parental Influencesmentioning
confidence: 99%
“…Family activities and habits: Engagement in sedentary activities by adults in the family or non-participation in physical activities, tend to influence children who view adults as role models. Reports from literature show that having obese or overweight parents and family members or friends , tend to influence children and is associated with obesity in children [171][172].…”
Section: Family and Parental Influencesmentioning
confidence: 99%